Severe sepsis and septic shock in Icelandic intensive care units. A nationwide study on epidemiology, outcome and management - Edda Vésteinsdóttir 1981- (2010)
Introduction: Severe sepsis and septic shock are important causes of intensive care unit admissions. The incidence is increasing and mortality remains high, 30-50%, despite advances in critical care medicine. The Surviving Sepsis Campaign was launched in 2004 with the goal of reducing mortality from sepsis by implementing evidence-based strategies. The aims of this study were to describe the epidemiology of severe sepsis and septic shock in a nationwide population and evaluate the compliance with treatment guidelines. Methods: This was a prospective, observational study of all adult patients admitted to Icelandic intensive care units, who were screened for the ACCP/SCCM criteria for severe sepsis or septic shock on admission. Data were collected from April 1st 2008 to March 31st 2009. Results: A total of 115 patients were admitted to the intensive care units because of severe sepsis or septic shock during the study year. The adult incidence in Iceland is 0.48/1000 inhabitants per year. The mean age was 65.4 years and males were 53%. The mean APACHE II score was 20.7. The 28-day mortality was 24.6% and 1-year mortality was 40.4%. The main sources of infections were: pulmonary (37%), abdomen (28%) and urinary tract (8%). Pathogens were gram-positive (39%), gram-negative (30%) and mixed (28%). No patient had sepsis caused by methicillin-resistant Staphylococcus aureus (MRSA) or fungi. Compliance to the resuscitation goals of the Surviving Sepsis Campaign ranged from 60-72% and all elements of the 6-hour Sepsis Bundle were adhered to in 35% of patients. Conclusions: The incidence of severe sepsis and septic shock in Icelandic intensive care units is similar to other recent epidemiological studies. Mortality is in the lower range of reported. The types of pathogens are consistent with current trends, with the exception of sepsis caused by MRSA and fungi, which are rare in Iceland. There is room for improvement in some aspects of sepsis management in Iceland.